Pengaruh informasi melalui Whatsapp ( WA) group terhadap sikap toleran di kalangan generasi muda buddhis - Situ Asih (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
This study aims to determine how much influence the information provided by religious leaders through the Wa Group has on the tolerance attitude of the young Buddhist generation. The sample in this study was the younger generation of Buddhists in Karanganyar Regency who opened 30 people. The research method used is a quantitative method where data collection techniques are carried out by distributing questionnaires to find out whether there is an influence of information through the Wa Group on the attitude of tolerance among the young Buddhist generation. The results showed a simple linear regression equation Y= 3.097 + 0.483 (X), this means that if X = 0, then Y is still 3.097 and positive in the same direction. If X increases then Y also increases and vice versa. For the correlation coefficient, it shows that there is a very high relationship between information through the WA Group and a tolerant attitude with a value of 0.932. The coefficient of determination obtained is 0.869, which means the magnitude of the influence of variable X on Variable Y is 86.9% with a significance level of 0.000